Răspuns :
1. a) √36 = 6
√6² = 6 (radicalul se anuleaza cu patratul)
8² = 8*8 = 64
0,6 = [tex] \frac{6}{10} [/tex]
Inlocuind, avem: [tex] \frac{6}{6+64} - \frac{6}{10} = \frac{6}{70} - \frac{42}{70} [/tex] (a doua fractie a fost amplificata cu 7), adica: [tex] \frac{6-42}{70} = \frac{-36}{70} = \frac{-18}{35} [/tex]
b) [tex] \frac{a}{b} : \frac{c}{d} = \frac{a}{b} * \frac{d}{c} [/tex], deci:
[tex] \frac{1}{20} : (- \frac{1}{10} )= \frac{1}{20} * (-\frac{10}{1} )=- \frac{10}{20}=- \frac{1}{2} [/tex]
Continuand, avem:
[tex]- \frac{1}{2} -(- \frac{3}{5}) =- \frac{1}{2} + \frac{3}{5} =- \frac{5}{10} + \frac{6}{10} = \frac{1}{10} [/tex]
√6² = 6 (radicalul se anuleaza cu patratul)
8² = 8*8 = 64
0,6 = [tex] \frac{6}{10} [/tex]
Inlocuind, avem: [tex] \frac{6}{6+64} - \frac{6}{10} = \frac{6}{70} - \frac{42}{70} [/tex] (a doua fractie a fost amplificata cu 7), adica: [tex] \frac{6-42}{70} = \frac{-36}{70} = \frac{-18}{35} [/tex]
b) [tex] \frac{a}{b} : \frac{c}{d} = \frac{a}{b} * \frac{d}{c} [/tex], deci:
[tex] \frac{1}{20} : (- \frac{1}{10} )= \frac{1}{20} * (-\frac{10}{1} )=- \frac{10}{20}=- \frac{1}{2} [/tex]
Continuand, avem:
[tex]- \frac{1}{2} -(- \frac{3}{5}) =- \frac{1}{2} + \frac{3}{5} =- \frac{5}{10} + \frac{6}{10} = \frac{1}{10} [/tex]